An improved adaptive intensity-hue-saturation method for the fusion of remote sensing images - Leung, Yee-Hong; Liu, J.; Zhang, J. (2014)
Extending on the adaptive intensity-hue-saturation (AIHS) method, an improved AIHS (IAIHS) method is proposed for pansharpening in this letter. Through the IAIHS method, the amount of spatial details injected into each band of the multispectral (MS) image is appropriately determined by a weighting matrix, which is defined on the basis of the edges of the panchromatic and MS images and the proportions between the MS bands. Experiments carried out on QuickBird and IKONOS satellite images show that the IAIHS method can maintain spectral quality while providing comparable spatial quality with the AIHS and additive wavelet luminance proportional methods. Â© 2004-2012 IEEE.